ANNA’S CONFLICTS IN GAINING HER EXISTENCE IN JODI PICOULT’S NOVEL ENTITLED MY SISTER’S KEEPER - DEWANTARA, FRANSISKUS XAVERIUS ANDAKA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Existentialism is a branch of philosophical thinking that begins with the human subject—not merely the thinking subject, but the acting, feeling, and living human individual. Related to the theory, researcher needs to grasp the basic meaning of existentialism. This study is carried out to establish connection between the theory of existence and how the main character in the novel find the meaning of her existence in this world.This study is a qualitative one, which was conducted by the study of literature then connect it with the related theory. This study is a literature analysis since this study uses the traits of the main character in the novel. The main character’s traits are analyzed using the existentialism theory of Jean Paul Sartre.The result of the study revealed that the main character in this novel was struggling to find what was the meaning of her existence in this world among people in her surrounding by pursuing her freedom to live a normal life through appealing herself to the court by the help of several people. In relation of the theory of existence by Jean Paul Sartre, the main character found that she existed to be an organ donor for her sister and that she wanted to gain freedom for her existence since she did not want to be an organ donor anymore.From the result of the study, some suggestions may be derived. The researcher should give attention to another conflict that main character in this novel experienced, which is the effect of her psychological conflict in her behavior and her everyday life. There are also many opportunities for the next researcher to use various approaches to analyze this novel, or using existentialism to analyze other literary works. Keywords: Existentialism, Literature Studies, Novel